Tuna baitfish and the pole and line industry in Kiribati - Rawlinson, N.J.F.; Milton, D.A.; Blaber, S.J.M. (Canberra, Australia Australian Centre for International Agricultural Research, 1992)
ACIAR Technical Report No. 24
Keywords: Baitfish; Tuna Fisheries